PENGARUH ALGORITMA LYZENGA DALAM PEMETAAN TERUMBU KARANG MENGGUNAKAN WORLDVIEW-2, STUDI KASUS: PERAIRAN PILU PAITON PROBOLINGGO - Jaelani, Lalu Muhamad; Laili, Nurahida; Marini, Yennie (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2015)
Mapping the coral reef ecosystems to support the coastal management can be carried out using a high-resolution satellite imagery. Various methods of sea bottom features extraction have been developed and can be implemented to support the mapping process, one of them is Lyzenga's algorithm. This algorithm requires a depth variation of the area. The objective of this research is to investigate the effect of Lyzenga's algorithm on coral reef mapping. In this research, we compared the classification results of coral ecosystem between image with and without Lyzenga's algorithm. The image classification with this algorithm showing the appearance of sea bottom features were more differentiated and turn into Lyzenga index values which have been free from the water column effect. It produced several classes, they were oceans, land, sand, and coral reefs. The estimated area of coral reefs ecosystems in the waters of Paiton Probolinggo based on Worldview-2 classification result was 8.26 ha. Mapping coral reef ecosystem by using a high-resolution satellite imagery was very helpful giving the visualization of a wider area than the field observations.